Mental Health Status of Nepalese Students during Novel Coronavirus Disease (nCOVID-19) Pandemic - Karmacharya, Isha; Shrestha, Shital; Paudel, Sachina; Adhikari, Laxmi; Bhujel, Kshitiz; Shakya, Karuna Laxmi (Europasian Journal of Medical Sciences, 2020)
Background: Since the wave of COVID-19, human life has highly been affected due to government endorsement of containment measures to control the disease. Education system has been held back and students are one of those who are greatly affected. Thus, this study attempts to find out the mental health status of Nepalese students during novel coronavirus Disease (nCOVID-19) pandemic. Methodology: A web-based cross sectional descriptive study was conducted from 9 May to 29 May 2020 among students of Nepal aged 18 years and above. A structured questionnaire was adopted from DASS-21. The obtained data were entered in Epidata v.3.1. and were analyzed using SPSS version 20. Descriptive frequency, percent and mean were calculated, and chi-square test was performed for bivariate analysis. Results: The mean age of the study participants was 21.4±2.7 years. This study found optimal mental health status among Nepalese students. Perceived family relationship however, showed statistical significance in all three mental health parameters (p<0.001); depression, anxiety and stress. Depression was found to be comparatively more in females (p<0.05), and those who held Bachelor’s and above degrees have shown presence of anxiety (p<0.05) and stress (p<0.05) relatively than those holding below degrees. Conclusion: Optimal mental health status among Nepalese students was found during the nationwide lockdown. Perceived family relationship however, showed statistical significance in all three mental health parameters. This is a wake-up call for education system to focus on socio-emotional skills – empathy and solidarity in easing this pandemic crisis confronted by young learners and their families.